Strength of extended stiffened end-plate bolted joints: Experimental and numerical analysis. (October 2021) - Gašić, Vlada; Arsić, Aleksandra; Zrnić, Nenad
Graphical abstract: Abstract: The analysis of behaviour of extended one-sided stiffened bolted end-plate moment connection is revisited here. On the basis of experimental tests, the behaviour of beam-to-column joint with and without stiffener is investigated. The stress distribution and deformation characteristics were determined and discussed with corresponding results of finite element analysis of joint behaviour. Furthermore, the extensive finite element simulations were carried out and the obtained results are discussed in this paper. The main analyzed parameters are the geometrical characteristics of the plates added to the beam-to-column joint. Their influence on joint resistance and stiffness is observed including the possibility of material cost optimization. Overall, the comparison of used approaches confirms their conjoint importance except for the postulation where the stiffener is assumed to behave as a strut in the joint. Also, there are some practical recommendations in design which can be used by engineers.